The role of proposal management systems in the production and service - Tamás, Peter; Varga, Attila (Journal of Production Engineering, 2021)
One of the most effective ways to increase the efficiency of logistics processes is to use different tools and methods of lean. Lean initially developed in the field of production, but today it has also become dominant in the service sector. The paper presents one of the basic tools of lean, i.e. the proposal management system, with the help of which the 8th type of loss, namely the non-utilization of the knowledge and creativity of the employees can be reduced. Theoretical background of the application of the tool, its application possibilities, and its application through a practical example are described.